Specific HR Training for Municipal and Housing and Public Facilities in the Republic of Kalmykia - O. V. Maksimchuk; S B. Boldyreva (Вестник Российского экономического университета имени Г. В. Плеханова)
Topicality of the research is stipulated by challenges of digitalization in the field of municipal and housing and public facilities, whose rate and effectiveness are seriously affected by regional specific features. The system of professional staff training for sectors of life-support in combination of vocational and higher education shall function with due regard to such specificities. The article includes a brief analysis of dynamics and structure of the population and provision of people with housing facilities, presents combined tables showing results of federal and regional programs concerning the Republic of Kalmykia, gives characteristics of municipal and housing and public facilities, makes conclusions and puts forward author’s recommendations. The goal of the research is to identify specific features of personnel training for the system of municipal and housing and public facilities in the Republic of Kalmykia and the necessity to train professional staff and develop SPO – VO system in view of potential challenges of digital transformation of municipal and housing and public facilities.